2020
DOI: 10.1093/ejo/cjaa075
|View full text |Cite
|
Sign up to set email alerts
|

Impact of oral-health-related quality of life and self-esteem on patients with missing maxillary lateral incisor after orthodontic space closure: a single-blinded, randomized, controlled trial

Abstract: Summary Background The maxillary lateral incisor is one of the teeth most likely to suffer agenesis, resulting in spacing between the central incisor and the canine. Objective To compare maxillary lateral incisor agenesis with space closure treatment versus non-treatment based on measurements of the self-perceived oral-health-related quality of life (OHRQoL) and self-esteem of the participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Andrade et al (2013) found no scientific evidence to support any treatment option for maxillary lateral incisor agenesis because they did not identify any randomised clinical trials. Pithon et al (2021) compared cases of orthodontic space closure versus cases with no treatment to determine the social impact and quality of life. The results were in favour of the cases treated with orthodontics, improving quality of life and self-esteem in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Andrade et al (2013) found no scientific evidence to support any treatment option for maxillary lateral incisor agenesis because they did not identify any randomised clinical trials. Pithon et al (2021) compared cases of orthodontic space closure versus cases with no treatment to determine the social impact and quality of life. The results were in favour of the cases treated with orthodontics, improving quality of life and self-esteem in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, a thematic synthesis approach was employed to synthesize the data. Thematic analysis is a suitable method for qualitative research [ 26 ]. The findings were summarized based on significant and prominent themes.…”
Section: Reviewmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the included studies. Out of these trials, five were RCTs [ 26 , 27 , 37 , 38 , 40 ], seven studies were cohort studies [ 13 , 24 , 28 , 32 , 34 , 35 , 39 ], and the other four studies had a cross-sectional design [ 17 , 31 , 33 , 36 ]. All of them were in English.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Oral health plays an important role in public health, and hypodontia might negatively affect a patient's dental function and esthetic. Subjects with missing teeth are more likely to suffer from malocclusion, insufficient alveolar bone growth, masticatory problems, reduced chewing ability, inarticulate pronunciation (speech), periodontal damage, and esthetic problems with changes in skeletal relationships and an unfavorable appearance, which might negatively affect patients' self-esteem, communication behavior, professional performance, and thus the quality of life and might need multidisciplinary treatment (3,14).…”
Section: Introductionmentioning
confidence: 99%